MENINGKATKAN KEMAMPUAN MENGENAL BILANGAN 1 SAMPAI 10 MELALUI MEDIA GAMBAR BAGI ANAK TUNARUNGU KELAS I DI SLB NEGERI TANJUNGPINANG - Esti - Hertanti (Jurnal Penelitian Pendidikan Khusus, 2013)
Improving the ability to know the concept of numbers from 1 to 10 with media images for deaf children in the special school class I Tanjungpinang Affairs The research was motivated by the problems that researchers found deaf children in special schools in the State Tanjungpinang. Children have difficulty in recognizing the concept of numbers I to 10, so that students are not able to recognize numbers. It is necessary for efforts to improve mathematics achievement in first grade deaf children in special schools Tanjungpinang State using media images. This research aims to prove that the media images can enhance learning mathematics achievement especially familiar numbers.Type of research is classroom action research, conducted in collaboration with colleagues form. Subjects were four deaf children in grades 1 SLB Tanjungpinang Affairs. The design of the study include: 1) planning, 2) implementation, 3) observations, 4) reflection. Activities undertaken in this study consisted of two cycles. In each cycle I held four meetings. The results showed that in the first cycle by using the image of the child begin to recognize there is an increase in the numbers I through 10. In the second cycle learning achievement of children is much more improved than in Cycle I. I cycle results demonstrate the ability of students to the concept of numbers from 1 to 10 has reached KKM 65. In order to OBTAIN results in line with expectations then continued on the second cycle. After the second cycle results were obtained over a specified KKM. Based on these results it can be concluded that the ability to recognize Increased numbers through media images. It is suggested that teachers should teach the deaf children in the teaching of mathematics in particular know the numbers using the media image. With media images of children with hearing impairment will be more receptive to learning and children interested in learning.